The monster - Nix, Garth; Williams, Sean, 1967- (New York : Scholastic Press, 2012)
Jaide and Jack Shield learn that they're troubletwisters, with powers they must use to stop the Evil from taking over our world. Before, they'd defeated the Evil through luck and intuition. Now though, Jaide and Jack will have to learn how to use their powers, and how to keep on their toes when evil forces return.
Kirkus Review, May 2012
6.2
3-6
Keywords: Magic -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Good and evil -- Juvenile fiction; Magic -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Good and evil -- Fiction; Fantasy; Magic -- Fiction; Twins -- Fiction; Siblings -- Fiction; Good and evil -- Fiction; Fantasy fiction; Fantasy fiction